2008
DOI: 10.1080/01639360802060140
|View full text |Cite
|
Sign up to set email alerts
|

Food Variety and Dietary Diversity as Indicators of the Dietary Adequacy and Health Status of an Elderly Population in Sharpeville, South Africa

Abstract: This cross-sectional, analytical study was a comprehensive health assessment focusing on dietary quality of 170 randomly selected elderly respondents in Sharpeville, South Africa. The methods included a sociodemographic, health food frequency questionnaire, 24h-recall questionnaires, and anthropometric and biochemical measurements. The low mean +/- standard deviation (SD) dietary diversity score (3.41 +/- 1.34) and food variety score (4.77 +/- 2.2) compared with poverty parameters confirmed household food inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 14 publications
10
64
2
Order By: Relevance
“…These scores were calculated for a reference period of seven days [22] . These dietary diversity scores were similar to those scores used in previous studies in other developing countries [8,14,23] . The nine nutritious food groups recommended by the FAO were used to classify food intakes categorically.…”
Section: Measurementssupporting
confidence: 69%
See 1 more Smart Citation
“…These scores were calculated for a reference period of seven days [22] . These dietary diversity scores were similar to those scores used in previous studies in other developing countries [8,14,23] . The nine nutritious food groups recommended by the FAO were used to classify food intakes categorically.…”
Section: Measurementssupporting
confidence: 69%
“…Furthermore, most of the unemployed are living in informal settlements in non-permanent zinc shacks with no land available for household gardens [12] . As a result, this poor community does not rely on agriculture as a household food security strategy and dietary diversity has been found to be poor in this area [13,14] . A previous study among the same sample of women indicated a prevalence of 34.3% for dyslipidaemia, 48.6% for hypertension and 45.0% for obesity [15] .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies from different populations and countries also found associations between overall dietary diversity and quality of the diet (21)(22)(23)(24)(25)(26)(27) . Nevertheless, a number of different groupings, classification systems and reference periods have been used.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary diversity has been known as a key index of high diet quality in various populations. [18][19][20] DDS evaluates the diversity within food groups that are often chosen based on healthy dietary guidelines. 21,22 The higher diversity in healthy food groups like vegetables and fruits could increase DDS but would not add substantial energy to the overall calorie content of the diet.…”
Section: Introductionmentioning
confidence: 99%